방사성폐기물 신분류기준을 고려한 중저준위 방사성폐기물 처분시설의 핵종재고량 예측 - 정강일(KangIl Jung), 정노겸(Noh Gyeom Jeong), 문영표, 정미선, 박진백(Jin Beak Park) (Journal of nuclear fuel cycle and waste technology (Online), 2016)
국내의 중저준위 방사성폐기물 처분시설에 대한 핵종량은 대부분의 방사성핵종에 대한 규명이 요구되어 진다. 본 논문에 서는 국내 경주 처분시설 부지에서 방사성폐기물의 처분을 위한 처분시설의 활용도 및 효율성 그리고 신분류기준을 반영한 핵종재고량을 예측하였다. 장기 방사성폐기물의 예측하기 위해 2014년까지 다양한 발생원별 방사성폐기물의 발생량과 발 생전망을 분석하였다. 예측된 핵종재고량 결과는 처분시설에 대한 안정적인 개발 및 Safety case의 구축하는데 기여할 것으 로 판단된다. To meet nuclear regulatory requirements, more than 95% individual radionuclides in the low- and intermediate-level radioactive waste inventory have to be identified. In this study, the radionuclide inventory has been estimated by taking the long-term radioactive waste generation, the development plan of disposal facility, and the new radioactive waste classification into account. The state of radioactive waste cumulated from 2014 was analyzed for various radioactive sources and future prospects for predicting the long-term radioactive waste generation. The predicted radionuclide inventory results are expected to contribute to secure the development of waste disposal facility and to deploy the safety case for its long-term safety assessment.